Commentary on structural inequities in global health research funding and practice - Saralees Nadarajah; Samuel Manda; Queensley C. Chukwudum (Frontiers in Public Health, 2026)
The testimonies gathered from researchers across Africa present a damning portrait of persistent structural inequities in how international research partnerships are conceived, funded, and executed. These firsthand accounts, spanning multiple countries and decades of experience, reveal patterns of exploitation, marginalization, and systemic bias that undermine both the integrity of scientific inquiry and the dignity of African researchers. What emerges is not merely a collection of isolated grievances but evidence of deeply embedded colonial-era power dynamics that continue to shape who controls knowledge production about Africa and its peoples. This commentary examines ten representative testimonies from the document, grouped thematically rather than sequentially so that the connections between them emerge clearly, analyzes the systemic issues they illuminate, and proposes concrete recommendations for funders, academic institutions, and researchers committed to equitable partnerships. The voices represented here speak to experiences across the research enterprise, moving from the framing of funding priorities, through the control of financial resources and data, to the marginalization of African intellectual leadership and the distortion of accountability practices.